The role of technology in structuring information seeking in health professionals - Borycki, Elizabeth Marie (ProQuest Dissertations & Theses, 2008)
The purpose of this dissertation was to investigate the relationship between technological structuration and health professional information seeking (i.e. choice of key sources of information, type of information and selection of information seeking tactics). A within group, laboratory, experimental study was conducted using two simulation environments. Thirty five novice nurses assessed and planned the care of two different patients in two different simulation environments: a paper environment (i.e. PR condition) and a hybrid paper-electronic environment (i.e. EPR condition—where part of the environment contained an electronic patient record). Two patient records were used in the study (i.e. patient A and B). Subjects were block randomized to receiving either patient A's or B's information first to prevent learning and order effects. Subjects were asked to “think aloud” in each of the environments and participated in a cued recall session to clarify any ambiguity in think aloud verbalizations. Subjects' verbalizations were audio recorded and their actions were video recorded. Data was transcribed and coded using model based coding and concepts from Newcomer Information Seeking Theory. Think aloud data was quantified. T-tests were performed to test for differences between the two conditions in terms of the amount of data accessed, choice of type of information and choice of information seeking tactic. Quantitative findings established relationships between technological structuration and aspects of information seeking. These findings revealed that technological structuration significantly decreased the amount of data accessed by subjects, subjects accessed significantly more non-electronic sources of information in the technologically structured environment (i.e. the EPR condition), and passive information seeking tactics were used more frequently in the EPR than the PR condition. The following new information seeking concepts emerged during protocol analysis of video, verbal and cued recall data: (a) two types of information—situational task and organizational information, (b) an information seeking tactic—monitoring, and (c) three new contextual factors—the quality of the information target, cognitive load, and task urgency. In summary, quantitative analyses suggested the presence of a relationship between technological structuration and aspects of information seeking. Qualitative analyses revealed Newcomer Information Seeking Theory requires extension.